Development of Character Education Assessment Instruments at Asta Learning Center Training Institution - Paramartha, I Putu Gede Indra; Candiasa, I Made; Widiartini, Ni Ketut (International Journal of Education, Culture, and Society, 2025)
Character education in vocational training institutions requires valid and reliable assessment instruments. At Asta Learning Center, the character assessment instrument has not been fully developed. This study aims to (1) identify the characteristics of the character education evaluation instrument at Asta Learning Center in relation to industrial needs, (2) examine the construction of character education variables based on empirical data, and (3) assess the validity and reliability of the developed character assessment instrument. This research uses the Research and Development (RnD) method, conducted from May to June 2024. The assessed character traits discipline, honesty, work ethic, independence, and social concern—are essential for developing competent employees. A Confirmatory Factor Analysis (CFA) approach, using SPSS 25.0 for Windows, was applied. The results indicate that the Likert-scale assessment instrument meets validity and reliability criteria. The small-scale trial (10 participants) showed a reliability of 0.761 and rtabel = 0.632, while the large-scale trial showed a reliability of 0.758 and rtabel = 0.367. The findings suggest that the developed instrument is valid, reliable, and suitable for use in Asta Learning Center's learning activities.